2008
DOI: 10.4088/jcp.v69n0715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulant Medication on Neuropsychological Functioning in Young Adults With Attention-Deficit/Hyperactivity Disorder

Abstract: consistent literature has documented significant associations between attention-deficit/hyperactivity Effects of Stimulant Medication on Neuropsychological Functioning in Young AdultsWith Attention-Deficit/Hyperactivity Disorder Objective:The main goal of this study was to evaluate the impact of stimulant medication on executive function deficits in a group of adolescents and young adults with attention-deficit/ hyperactivity disorder (ADHD; DSM-III-R criteria).Method: Male and female subjects aged 15 to 25 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 30 publications
8
33
1
1
Order By: Relevance
“…Taken together, these findings support the search for safe and effective treatments to help address WM deficits in individuals with and without ADHD. The absence of associations between CANTAB and BRIEF/BRIEF-A based definitions of WM are consistent with previous reports documenting similar absence of associations between psychometrically and behaviorally defined assessments of executive function deficits [42]. Taken together, these findings indicate that CANTAB and BRIEF/BRIEF-A definitions of WM are independent of each other.…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, these findings support the search for safe and effective treatments to help address WM deficits in individuals with and without ADHD. The absence of associations between CANTAB and BRIEF/BRIEF-A based definitions of WM are consistent with previous reports documenting similar absence of associations between psychometrically and behaviorally defined assessments of executive function deficits [42]. Taken together, these findings indicate that CANTAB and BRIEF/BRIEF-A definitions of WM are independent of each other.…”
Section: Discussionsupporting
confidence: 90%
“…Methylphenidate not only reduces core symptoms of ADHD, but also improves many functional domains via blockage of the transporter for dopamine (DA) and norepinephrine (NE; Hechtman et al, 2004;Coghill, 2010). Moreover, some studies have demonstrated that methylphenidate can improve executive function deficits, including sustained attention (Bouffard et al, 2003;Turner et al, 2005;Wilson et al, 2006;Biederman et al, 2008b), verbal learning (Biederman et al, 2008b), verbal memory (Kurscheidt et al, 2008) and response inhibition (Aron et al, 2003;Boonstra et al, 2005) in adults with ADHD. Moreover, in a head-to-head comparison study in healthy adults, Marquand et al (2011) found that the effects of methylphenidate and atomoxetine on working memory were context-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Biederman et al, (2008b) showed that medication did not normalize Stroop interference control in young adults with ADHD. In our study, the Interference RT of the On Med group was normalized.…”
Section: Neuropsychological Assessment Of Adhd-diagnosed College Studmentioning
confidence: 99%
“…In this case, MPH did improve performance of ADHD adults on the Tower of London, but not on the verbal fluency task. Biederman et al, (2008b) administered a battery of tests to non-ADHD subjects and separate groups of ADHD patients who were either on or off medication. They found the largest beneficial effects on sustained attention (vigilance) and verbal learning, whereas stimulants did not significantly improve measures of interference (i.e.…”
Section: Neuropsychological Assessment Of Adhd-diagnosed College Studmentioning
confidence: 99%